Prevalence and Relevance of Pre-Existing Anti-Adeno-Associated Virus Immunity in the Context of Gene Therapy for Crigler-Najjar Syndrome - Aronson, Sem J; Veron, Philippe; Collaud, Fanny; Hubert, Aurélie; Delahais, Virginie; Honnet, Géraldine; de Knegt, Robert J; Junge, Norman; Baumann, Ulrich; Di Giorgio, Angelo; D'Antiga, Lorenzo; Ginocchio, Virginia M; et al. (Human gene therapy, 2019)
Adeno-associated virus (AAV) vector-mediated gene therapy is currently evaluated as a potential treatment for Crigler-Najjar syndrome (CN) (NCT03466463). Pre-existing immunity to AAV is known to hinder gene transfer efficacy, restricting enrollment of seropositive subjects in ongoing clinical trials. We assessed the prevalence of anti-AAV serotype 8 (AAV8) neutralizing antibodies (NAbs) in subjects affected by CN and investigated the impact of low NAb titers (<1:5) on liver gene transfer efficacy in an passive immunization model. A total of 49 subjects with a confirmed molecular diagnosis of CN were included in an international multicenter study (NCT02302690). Pre-existing NAbs against AAV8 were detected in 30.6% (15/49) of screened patients and, in the majority of positive cases, cross-reactivity to AAV2 and AAV5 was detected. To investigate the impact of low NAbs on AAV vector-mediated liver transduction efficiency, adult wild-type C57BL/6 mice were passively immunized with pooled human donor-derived immunoglobulins to achieve titers of up to 1:3.16. After immunization, animals were injected with different AAV8 vector preparations. Hepatic vector gene copy number was unaffected by low anti-AAV8 NAb titers when column-purified AAV vector batches containing both full and empty capsids were used. In summary, although pre-existing anti-AAV8 immunity can be found in about a third of subjects affected by CN, low anti-AAV8 NAb titers are less likely to affect liver transduction efficiency when using AAV vector preparations manufactured to contain both full and empty capsids. These findings have implications for the design of liver gene transfer clinical trials and for the definition of inclusion criteria related to seropositivity of potential participants.